Supplementation of corn-soybean based layer diets with different levels of acid protease - Satrijo Widi Purbojo; Edwin S Luis; Reny Debora Tambunan; Dicky Pamungkas (Jurnal Ilmu Ternak dan Veteriner, 2004)
The aim of this research was held in Institute of Animal Science farm, University of the Philippines Los Banos, was to know the effects of acid protease supplementation in layer diets. Ninety-four-week old pullets were caged individually. Five treatments were randomly arranged to 95 pullets following a completely randomized design. Each treatment was replicated 19 times. The feeding trial lasted for 16 weeks. The same management practices were provided to all treatments throughout the feeding period. Pullets were fed once a day in the morning and clean drinking water was available to the pullets at all times. A basal layer diet that contained 18% crude protein (CP) and 2800 Kcal ME/kg supplemented with required vitamins, minerals and amino acids were formulated. The diets with reduced protein of 17% and 2800 kcal ME/kg was also formulated. The diet with the reduced crude protein was supplemented with different levels of protease (0.05, 0.075 and 0.1%). Six birds from each treatment were randomly selected and placed in individual digestion cages. They were fed with their respective diets with chromic oxide as indicator for 7 days. Chromic oxide was added to the different diets at 0.2%. On the 3rd to 6th day of feeding, feces were collected using stainless fecal trays installed under each cage. At the end of the collection period, fecal samples collected from each replicate of treatment were dried then subjected to proximate analysis and chromic oxide determination. Result showed that no significant difference on biweekly feed consumption and overall observations. Reduced CP + 0.1% protease was the highest on the hen day production (93.75%) and the lowest of feed conversion (1.85) while reduced CP + 0.075% protease was the highest of egg weight (58.82 g) and eggshell thickness (0.392 mm). There was no significant difference on digestibility coefficient.   Key words: Acid protease, layer diets, supplementation